A Brief History of the Bracero System and its Impact on Farm Labor in California - American Friends Service Committee::::::; Kirke Wilson:::::: (1967)
A document describing the history of the Bracero System in California and the various ways it impacted farm labor in California. Also describes the end of the Bracero System and the transition to a different agricultural labor system.